2013
DOI: 10.1007/s10552-013-0256-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in ARID5B and CEBPE are childhood ALL susceptibility loci in Hispanics

Abstract: Recent genome-wide studies conducted in European Whites have identified novel susceptibility genes for childhood acute lymphoblastic leukemia (ALL). We sought to examine whether these loci are susceptibility genes among Hispanics, whose reported incidence of childhood ALL is the highest of all ethnic groups in California, and whether their effects differ between Hispanics and non-Hispanic Whites (NHWs). We genotyped 13 variants in these genes among 706 Hispanic (300 cases, 406 controls) and 594 NHW (225 cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 18 publications
8
36
1
Order By: Relevance
“…Most GWAS, until recently, have identified risk loci using only European-origin populations. Variant polymorphisms located within the ARID5B, IKZF1, and CEBPE genes have reported strong risk associations in multiple GWAS [34][35][36][37][55][56][57]. Our study provides some confirmation of previously discovered genetic markers associated with childhood ALL, which also validated our case-control set for further exploration.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Most GWAS, until recently, have identified risk loci using only European-origin populations. Variant polymorphisms located within the ARID5B, IKZF1, and CEBPE genes have reported strong risk associations in multiple GWAS [34][35][36][37][55][56][57]. Our study provides some confirmation of previously discovered genetic markers associated with childhood ALL, which also validated our case-control set for further exploration.…”
Section: Discussionsupporting
confidence: 80%
“…The study population only included 32 childhood ALL patients, of which 14 were male, and did not find any significant results. Other hematologic malignancies studies on acute myeloid leukemia [56] and Hodgkin disease [32] have found no risk associations with HFE variants, and a myelodysplastic syndrome study [57] revealed a positive association, which was not been replicated in a different population sample [58].…”
Section: Hfe Variants and Childhood Leukemia Riskmentioning
confidence: 87%
See 2 more Smart Citations
“…To this point, the well-described [11] higher rates of relapse and poorer survival of Hispanic children with acute lymphoblastic leukemia (ALL) have recently been linked to percentage of Native American ancestry using principal component analysis (PCA) [12]. Furthermore, genomewide association studies (GWASs) have linked polymorphisms in the ARID5B gene to both elevated risk of developing ALL and risk of relapse after multiagent chemotherapy in this population [13,14]. Despite these advances, whether these genetic associations are responsible for variations in response to particular antineoplastic agents remains unclear.…”
mentioning
confidence: 99%